(untitled) (CAHIERS MAGELLANES-NS, 2024)
In today's competitive banking landscape, banks are striving to attract and retain customers by offering innovative services through e-banking. New electronic delivery channels are being integrated into existing services regularly, making banking accessible with just a click. Despite the growing popularity of e-banking, many people in India remain unaware of it, and those who are informed often hesitate to use it due to concerns like password hacking, privacy, and security issues. This study examines customer awareness of e-banking and their expectations. The findings reveal that while customers are generally satisfied with the quality of e-banking services, they face technical, administrative, and procedural challenges. To further promote e-banking, banks must prioritize delivering high-quality customer service. "Quality in service" and "customer satisfaction" are critical elements that require focused attention to successfully promote these services.